Penerapan Metode Small Sided Games terhadap Keterampilan Shooting Peserta Didik pada Ekstrakurikuler Futsal - Achmad Aldi Febrianto; Nanang Indriarsa (Journal on Education, 2024)
This research aims to determine the effectiveness of implementing the small sided games method on students' shooting skills in extracurricular futsal at Al-Islam Krian High School. This research is a Quasi Experimental research. The design used in this research is one group pretest-posttest. The sample was 30 students who took active extracurricular activities in futsal. Data was obtained by carrying out a test using a basic shooting technique skills test instrument using the back of the foot directed towards a goal that already has a target point. Based on data analysis through paired sample T-test which is seen through the t-count value with t-table of -6.654 > 1.699 and a significance value of 0.00 < 0.05, then H0 is rejected and Ha is accepted, so there is a difference in students' shooting skills between before and after being given treatment, namely small sided games. The percentage increase in students' shooting skills using the small side game method is in the low category, namely 25.82%.